Magic and the Dignity of Man Pico della Mirandola and His ‹i›Oration‹/i› in Modern Memory - Copenhaver, Brian P. (Harvard University Press, 2019)
Pico della Mirandola, one of the most remarkable thinkers of the Renaissance, has become known as a founder of humanism and a supporter of secular rationality. Brian Copenhaver upends this understanding of Pico, unearthing the magic and mysticism in the most famous work attributed to him, The Oration on the Dignity of Man.